Liberal Institutes and the Consolidation of Neoliberal Hegemony in Latin America and Brazil (London Journal of Research In Humanities and Social Sciences, 2023)
This article aims to analyze the connections between the advance of the right-wing neoliberalism in Latin American countries, notably in Brazil, and the networks of liberal institutes. We specifically examine the North American think tank Atlas Network and the partner networks of this organization operating in Latin America and in Brazil. It is a movement deeply articulated by these networks at a global level, grounded on the Hayekian ideological battle of diffusion of the neoliberal rationality in order to legitimize and pave the way for the unbridled escalation of capital, which commodifies society and brutally expropriates workers from rights and social policies, by means of orthodox changes in the political, legal, ideological and social fields.
Keywords: think tanks network. liberal institutes. ideological battle. neoliberalism.